A cross-sectional observational study to establish the association between ECOG performance status and age and administration of doublet or triplet chemotherapy containing Xeloda® (capecitabine) in advanced gastric cancer patients - Molina, Raquel; Jiménez, Encarnación; Macarulla, et al., Teresa (European Journal of Oncology and Environmental Health, 2014)
Background: Selection of treatment for advanced gastric cancer (AGC) correlates with age and ECOG PS. This study was carried out to analyze whether previously mentioned variables are relevant for the choice of doublet or triplet regimens with capecitabine (Xeloda®) and determining prognosis. Methods: Multicenter, cross-sectional, observational study in patients with AGC who received at least 2 cycles of capecitabine-based doublet or triplet chemotherapy, with or without measurable disease. Results: A total of 175 patients were evaluated. Median age 65.5 (56-72) years, male: 68% ECOG 0/1/2: 32.7%/55.6%/11.1%; 33% underwent doublet and 67% triplet chemotherapy. Tumor histology: adenocarcinoma (27.4%), signet ring cell carcinoma (28%) and others (41.7%). Most common sites of metastases: lymph node (46.2%), peritoneum (39.4%) and liver (36.6%). Multivariate analysis demonstrated that age ≤64 (OR 0.447; p=0.016) and ECOG 0 (vs 2) (OR 0.253; p=0.016) were risk factors for the choice of triplet chemotherapy, and failed to show an association between ECOG 1 and regimen. With regard to the secondary endpoints, age was statistically related with treatment selection when considered numerical (p<0.01) or categorical (p<0.05) and ECOG PS also showed this relationship (p<0.01). Main grade 1/2 capecitabine-related toxicities: diarrhea (11.4%), mucositis (7%), hand-foot syndrome (4.6%) and emesis (4%). Most frequent grade 3 were diarrhea in 4.6% and emesis, asthenia and febrile neutropenia in 2.3%. No toxicity grade 4 occurred. Conclusions: Age ≤64 years and ECOG 0 are related factors of choice of capecitabine-based triplet chemotherapy in AGC.